Cross-cultural adaptation and reliability of pediatric sleep questionnaire in assessment of sleep-disordered breathing in the Malay speaking population - Abdul Latif, Hasniah; Ab Rahman, Jamalludin; Abd. Wahab, Norrashidah; Mohamed Zainudin, Norzila; Kassim, Asiah; Awang, Rus Anida; Abdullah, Ahmad Fadzil; Zainal, Ramli; Hussain, Samsinah (Zhejiang University * School of Medicine Children's Hospital, 2011)
BACKGROUND: Sleep-disordered breathing (SDB) is common but often underdiagnosed in children. The Pediatric Sleep Questionnaire developed by University of Michigan, USA (English UM PSQ) has high sensitivity and specificity in identifying children with sleep-disordered breathing. This study aimed to translate and adapt the English UM PSQ into Malay language as a screening tool to assess SDB among the Malay speaking population. The second objective was to determine the psychometric measurements of the translated UM PSQ (Malay UM PSQ). METHODS: The Malay UM PSQ was translated through forward-backward translation techniques by two independent accredited bodies and reviewed by a panel of experts. The questionnaire was tested in two phases. The respondents were from hospital staffs with children and parents of primary school children aged 6-10 years. The reliability of questionnaires was measured by Cronbach's α and Kappa (κ) statistics. RESULTS: The overall scale of internal consistency of the Malay UM PSQ was good, i.e., Cronbach's α = 0.760 (α = 0.457, 0.608 and 0.688 for snoring, sleepiness and behavioral domains respectively). The English UM PSQ also had good internal consistency at α = 0.753 (α = 0.589, 0.524, to 0.793 for snoring, sleepiness and behavioral domains respectively). Test-retest reliability for most items was good with correctness of >85.0% in all items. Only one item was seen in the Malay UM PSQ with κ=0.348, while the remaining ranged from κ=0.489 to 0.811. For the English UM PSQ, κ ranged from 0.660 to 0.945. CONCLUSION: Both English and Malay UM PSQ have acceptable psychometric measurement properties as screening tools to assess SDB in the Malay speaking population.